EXPLORING EDUCATION MODEL OF PESANTREN BASED LOCAL WISDOM: A CASE STUDY AT PESANTREN OF NURUL QARNAIN JEMBER - Erfan Habibi; Muhammad Noor Harisudin; Moch. Chotib; Abd. Halim Soebahar; M. Holil (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
This research was conducted at the Pesantren of Nurul Qarnain Jember. Based on initial observations, it was found that this Islamic boarding school has a peculiarity, namely being able to integrate local wisdom values in the education carried out in it, for example, in teaching Sufism, students are taught about the importance of harmony between themselves, society, and the environment. In addition, prayer activities involving students in Nasyid and Hadrah traditional art performances were packaged with the title Majlis Al Wishol. Through the qualitative-descriptive research conducted, it was found that the approach of integrating local values with Islamic teachings was proven to increase students' awareness of the importance of preserving cultural heritage while adhering to religious principles. Furthermore, the results of the evaluation showed that teaching methods involving local cultural practices, such as traditional performing arts and environmental wisdom, created a more engaging learning atmosphere.